Does Ukraine need a new Black Sea Grain Initiative? - Dodd, Emma; Glauber, Joseph W.; Welsh, Caitlin (Center for Strategic and International Studies, 2025)
Nascent agreements over safety of navigation on the Black Sea indicate Russia’s desire to restart the Black Sea Grain Initiative, but Ukraine has already secured—and increased—its agricultural exports without Russia’s cooperation.